Research Infrastructures in the Digital Humanities - Žic Fuchs, Milena (Array, 2011)
This contribution is an overview of the ESF Science Policy Briefing under the title Research Infrastructures in the Digital Humanities. This Science Policy Briefing was initiated and completed under the auspices of the Standing Committee for the Humanities (SCH) with professor Claudine Mulin as chair of the SCH Expert Working Group on Research Infrastructures. This Executive Summary presents the main points of the Science Policy Briefing that tries to formulate priorities for policy and research: (1) State of the Art and Needs ; (2) Physical and Digital RIs ; (3) Strategic Directions ; (4) Partnerships and Networking ; (5) Academic Recognition ; (6) Dissemination and Outreach ; (7) Evaluation of RIs.